Development and evaluation of sexual assault training for emergency department staff in Ontario, Canada. (November 2018) - Du Mont, Janice; Solomon, Shirley; Kosa, Sarah Daisy; Macdonald, Sheila
Abstract: Objective: The purpose of this evaluation was to assess the efficacy of a training in improving competence to address sexual assault among Emergency Department (ED) staff, as well as to compare in-person and online training modalities. Methods: A total of 1564 staff from 76 EDs in acute care hospitals across Ontario participated in either on-site (n = 828 staff) or online (n = 736 staff) training sessions, of whom 1366 (87%) completed both a pre- and post-training questionnaire. Mean pre- and post-training scores measuring perceived competence in responding to victims/survivors of sexual assault were compared using paired t -tests. The mean gain score for in-person and online training was then compared using the Mann-Whitney U test. Finally, in-person and online participants' ratings of the training content and delivery were compared using the Mann-Whitney U test. Results: There were significant improvements for all 16 self-reported measures of competence following training. The mean gain in knowledge and skills was higher for in-person training participants. Participants in the in-person modality more strongly agreed that the information they learned would help in providing care for sexual assault victims/survivors, and were more satisfied with the training overall. However, these participants less strongly agreed that there was an appropriate amount of time allotted for the scope of material presented. Conclusions: Overall, the training led to immediate improvements in ED staff perceived understanding and ability to address the needs of victims/survivors of sexual assault, with particular advantages to the in-person training.